2018
DOI: 10.1002/tie.21967
|View full text |Cite
|
Sign up to set email alerts
|

Merger and acquisition motives and outcome assessment

Abstract: Research on merger and acquisition (M&A) outcome often focuses on tangible financial results and the reaction of stock markets. This research attempts to provide a more accurate assessment of M&A performance by linking tangible as well as intangible M&A motives to outcome assessment. The theoretical framework is based on evaluation theory. We analyze four case studies of international M&As conducted by European companies. The findings indicate that M&A outcome can be more accurately measured by aligning it wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 58 publications
1
21
0
1
Order By: Relevance
“…In their research, Cheny and Gayle (2018) found that financial synergy will have a significant positive impact on firm reputation because both companies will get greater market access. In the research of Hassan et al, (2018) it was found that the disclosure of information on the purpose of the acquisition, especially the openness of the goal of financial synergy, has a significant effect on firm reputation because the disclosure of information will provide a clear goal for the company to pursue the acquisition goals, making it easier for management to pursue the acquisition goals that make the company, in the eyes of investors, more reputable. Jenner et al, (2017) found that if the purpose of acquisition is financial synergy, this would have a significant positive impact on firm reputation because if a company made full disclosure of information, financial synergy would provide security value to investors that the company is open to improving the financial problems faced and this increases the value of firm reputation in the eyes of investors.…”
Section: Financial Synergy and Firm Reputationmentioning
confidence: 99%
See 2 more Smart Citations
“…In their research, Cheny and Gayle (2018) found that financial synergy will have a significant positive impact on firm reputation because both companies will get greater market access. In the research of Hassan et al, (2018) it was found that the disclosure of information on the purpose of the acquisition, especially the openness of the goal of financial synergy, has a significant effect on firm reputation because the disclosure of information will provide a clear goal for the company to pursue the acquisition goals, making it easier for management to pursue the acquisition goals that make the company, in the eyes of investors, more reputable. Jenner et al, (2017) found that if the purpose of acquisition is financial synergy, this would have a significant positive impact on firm reputation because if a company made full disclosure of information, financial synergy would provide security value to investors that the company is open to improving the financial problems faced and this increases the value of firm reputation in the eyes of investors.…”
Section: Financial Synergy and Firm Reputationmentioning
confidence: 99%
“…In the research of Hassan et al, (2018) they found that the information disclosure relating to acquisition goals, especially the openness of financial synergy goals, has a significant effect on firm reputation because disclosure of information will provide clear goals for companies to pursue the acquisition goals, making it easier for management to pursue the acquisition goals which makes the company in the eyes of investors more reputable. H2 = Financial synergy have a significant effect on firm reputation.…”
Section: Financial Synergy and Firm Reputationmentioning
confidence: 99%
See 1 more Smart Citation
“…The linkage of M&A motive and the performance outcomes of M&A is necessary and has been proved by some previous studies (Hassan et al, 2018;He & Wang, 2014;Liu et al, 2010;Markelevich, 2003;Paulone, 2013;Rabier, 2017) with various methods and results. Referring to previous studies (Berkovitch & Narayanan, 1993;Fernández & Baixauli, 2003;Kiymaz & Baker, 2008;Seth et al, 2000), this study groups M&A motives based on market reactions at M&A announcements period then examines the effects of M&A motive differences on the company long-term performance.…”
Section: Hypothesis Developmentmentioning
confidence: 94%
“…Market competition is becoming more intense day by day, due to technological developments, liberalisation stemming from globalisation, and the development of an increasing number of financial instruments. M&As are being increasingly used by companies with tangible and intangible motivations (Hassan et al, 2018), so that firms can benefit from access to new markets, demographics, and location (Boateng et al, 2008). A good portion of all M&A activity occurs between nations.…”
Section: Literature Reviewmentioning
confidence: 99%